Impact of Milk Enrichment with Manganese Supplement in Organic and Inorganic Forms on Performance, Biochemical, Antioxidant Parameters and Feeding Behavior of Suckling Calves - Ayda Teymouri; Abdolhakim Toghdory; Taghi Ghoorchi; Mohammad Asadi (پژوهشهای علوم دامی ایران)
Introduction: Newborn calves have special needs to accelerate their growth performance and improve their immune systems. Minerals are one of the most important metabolic improvers that can help the health of calves at overnutrition levels. Manganese is a necessary trace mineral that is a key ingredient in the metabolism of carbohydrates, lipids and, proteins, as well as playing an important role as a cofactor in the activity of several enzyme systems such as superoxide dismutase (MnSOD) activity, bone development (mucopolysaccharide synthesis) and blood cell regeneration. Manganese plays several important roles in the immune system, including its involvement in antioxidant pathways, its contribution to phagocytic activity, and its role in maintaining the structural integrity of epithelial barriers against infections. Manganese can be supplemented in both inorganic and organic forms, each with differing levels of bioavailability and absorption. Therefore, this study was conducted to investigate the impact of milk enrichment with manganese supplements, in both organic and inorganic forms, on the performance, biochemical and antioxidant parameters, and feeding behavior of suckling calves. Materials and Methods: 24 newborn calves were randomly divided into 3 groups with 8 replications. Experimental treatments include: 1) control group (without manganese supplementation), 2) Adding mineral manganese supplement to milk consumption and 3) Adding organic manganese supplements to milk consumption. The amount of manganese used in the milk of each calf was 30 mg per day. Manganese is dissolved in milk and consumed by calves. Calves were milked twice in the morning and evening and had free access to water and starter feed during the day. The length of the trial period was 63 days. Calves were weighed every 21 days. The amount of feed consumed and post-feed was recorded daily. To measure blood metabolites including biochemical parameters, concentration of blood elements, antioxidant status and activity of liver enzymes, blood samples were taken from calf vein on day 60. Finally, during the 61st to 63rd days of the experimental period, nutritional behaviors were measured for a duration of 48 hours. Data analysis was done using SAS statistical software version 9/1 (2004) and comparisons of means were done with Tukey's test at a significance level of 5 percent.Results and Discussion: The obtained results showed that the calves fed with milk enriched with manganese in organic and inorganic forms compared to the calves of the control group, a significant improvement in final weight, period weight gain, daily weight gain and dry matter consumption was observed. The use of organic and inorganic forms of manganese in the feeding of suckling calves did not have a significant effect on the feed conversion ratio of the calves. There was no significant effect on the amount of iron, zinc, copper, calcium and phosphorus of different treatments. The amount of plasma manganese in the treatment using organic manganese was associated with a significant increase compared to the treatment using inorganic manganese and the control treatment. The use of organic and mineral sources of manganese in the feeding of calves had no significant effect on triglyceride, cholesterol, urea, globulin and the ratio of albumin to globulin in the blood of calves. Organic and mineral sources of manganese increased the amount of glucose, total protein and albumin in the blood, so that the most significant increase was seen in the treatment of organic manganese users. Inorganic and organic forms of manganese did not cause significant changes in the amount of malondialdehyde, aspartate aminotransferase, and alkaline phosphatase in the blood of supplement consuming groups. In treatments using manganese, there was a significant decrease in total antioxidant status and a significant increase in the amount of catalase, superoxide dismutase, and alanine aminotransferase. The use of manganese supplement in organic and inorganic forms had no effect on the nutritional behaviors of calves such as milking, feeding, rumination, jaw rest, drinking water, unusual behavior, standing and lying down.Conclusion: Enriching milk with manganese supplement in organic and inorganic forms improved performance, weight gain, dry matter intake, total antioxidant status, and catalase and alanine aminotransferase and biochemical status in groups consuming milk containing manganese. Based on the results of this study, it is recommended to supplement the milk of newborn calves with 30 mg of organic manganese. Organic manganese showed improved effects on key parameters, including plasma manganese concentration, glucose levels, total protein, and superoxide dismutase (SOD) activity.